2016
DOI: 10.1182/blood-2015-11-679639
|View full text |Cite
|
Sign up to set email alerts
|

Early cytomegalovirus reactivation remains associated with increased transplant-related mortality in the current era: a CIBMTR analysis

Abstract: Key Points Cytomegalovirus after bone marrow transplantation remains associated with lower survival but not prevention of leukemia relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

23
385
7
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(444 citation statements)
references
References 40 publications
(79 reference statements)
23
385
7
2
Order By: Relevance
“…This weakness in the study design seriously questions the reliability of the results of this study. 1 In contrast, we and others have published that CMV reactivation correlates with substantially improved reduction of relapse incidence in patients with AML after transplant. [2][3][4][5][6][7][8][9][10] The antileukemic effect of CMV reactivation is pronounced in AML and chronic myeloid leukemia (CML), but is detectable to a lesser extent in myelodysplastic syndrome (MDS), acute lymphoblastic leukemia (ALL), non-Hodgkin lymphoma, and pediatric acute leukemia.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…This weakness in the study design seriously questions the reliability of the results of this study. 1 In contrast, we and others have published that CMV reactivation correlates with substantially improved reduction of relapse incidence in patients with AML after transplant. [2][3][4][5][6][7][8][9][10] The antileukemic effect of CMV reactivation is pronounced in AML and chronic myeloid leukemia (CML), but is detectable to a lesser extent in myelodysplastic syndrome (MDS), acute lymphoblastic leukemia (ALL), non-Hodgkin lymphoma, and pediatric acute leukemia.…”
mentioning
confidence: 92%
“…Teira et al, Green et al, and Takenaka et al found that CMV reactivation was associated with an increased NRM rate. 1,3,4 Moreover, Takenaka et al and Teira et al reported that the OS rate was decreased. 1,4 In contrast, Jang et al as well as our group found that, in single-center studies, CMV reactivation was associated with an improved OS rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Опреде-лены наиболее значимые факторы риска ЦМВ-ин-фекции/болезни: серологический статус донора/ реципиента, развитие реакции «трансплантат против хозяина», использование различных типов антилим-фоцитарных антител, Т-клеточная деплеция ex vivo, трансплантация от неродственного или не полностью совместимого донора [6,[11][12][13][14]. Несмотря на то, что в большинстве исследований развитие ЦМВ-инфекции после ТГСК -это прогностически неблагоприятный фактор в отношении выживаемости, в ряде современ-ных работ показана возможная роль ЦМВ в протекции против рецидива лейкоза [15][16][17][18][19].…”
unclassified
“…However, CMV is a leading cause of viral complications in immunocompromised individuals (2). This is particularly evident in the absence of CMV-specific immunological memory, including in CMV-seropositive HSCT recipients (R ϩ ) who receive a transplant from a seronegative donor (D Ϫ ) and are at a higher risk of CMV reactivations and associated complications, including enterocolitis and pneumonitis (3)(4)(5). Current therapeutic strategies to control CMV reactivation in HSCT recipients predominantly involve the preemptive administration of ganciclovir to control CMV following detection of viral reactivation (6).…”
mentioning
confidence: 99%